Comparison of Time to Recurrence of Instability After Open and Arthroscopic Bankart Repair Techniques. Issue 6 (23rd June 2016) - Virk, Mandeep S.; Manzo, Richard L.; Cote, Mark; Ware, James K.; Mazzocca, Augustus D.; Nissen, Carl W.; Shea, Kevin P.; Arciero, Robert A.
Background: The results of open and arthroscopic instability repairs have been shown to be equivalent in recent literature. Purpose: To compare the time to recurrence (TTR) of instability and disease-specific outcome measures in patients undergoing open and arthroscopic Bankart repair. Study Design: Cohort study; Level of evidence, 3. Methods: Patients with recurrent traumatic anterior shoulder instability and a Bankart lesion on diagnostic arthroscopy underwent either open Bankart repair (OB) or arthroscopic Bankart and suture capsulorrhaphy (ABSC) using suture anchors. There was a minimum follow-up of 24 months. The primary outcome measures included Western Ontario Shoulder Instability Index (WOSI) score and time to recurrence of instability (dislocation or subluxation). Rowe score, Simple Shoulder Test, Constant score, American Shoulder and Elbow Surgeons (ASES) score, and Short Form–12 (SF-12) score were also compared. Results: A total of 82 shoulders in 80 patients (ABSC, n = 58; OB, n = 24) were evaluated at a mean of 39 months postoperatively. There were 4 clinical failures in the OB group (4 dislocations) and 7 clinical failures in the ABSC group (2 dislocations and 5 subluxations; P = .72 vs OB). The mean time to recurrence of postoperative instability was significantly shorter in the ABSC group (12.6 ± 2.7 months) compared with the OB group (34.2 ± 12 months; P = .04). The WOSI score in the OB group (265 ± 48.1) was better but not statistically significantly compared with the ABSC group (449.8 ± 63.8; P = .06). Conclusion: The time to recurrence of instability after open Bankart repair is significantly longer compared with arthroscopic Bankart repair. Clinical Relevance: Delayed time to recurrence after open Bankart repair suggests that the open technique may be more suited to withstand the high stress and demands of a heavy-duty profession (contact athletes and heavy manual labor).